Estrategias para impulsar el turismo en la parroquia Toacaso, cantón Latacunga, provincia Cotopaxi, año 2022 - Vargas Guamán, Gladys Lisbeth (2023)
In the present research study, the elaboration of strategies to promote tourism in the Toacaso parish was proposed, in order to publicize the tourist benefits of the parish, for the fulfillment of the objectives, the mixed methodology was worked on, which was carried out using the techniques of bibliographic research, documentary and field analysis at a descriptive research level. In the first place, a situational diagnosis was made in 4 areas: economic, sociocultural, environmental and tourism, obtaining as a result, the part of the population is indigenous where their main economic income is agriculture, livestock, fish farming and trade. In addition, the study of the offer was defined through the analysis of the PDOT and the tourist cadastre, where 25 attractions were identified, of which 10 are natural and 15 cultural, which allows establishing the tourist potential of the Toacaso parish. To determine the demand, the calculation of the sample was carried out and surveys were applied, which allowed considering key elements for the approach of strategies, improvement of tourist activities, strengthening and development of the locality. Finally, strategies were generated through the SWOT and CPES analysis, analyzing the internal and external factors and prioritization of critical nodes, which will allow promoting tourism in the parish and thereby boost the economy, later promoting them through various means of communication at the local, national level. and international. Keywords Strategies, SWOP, CPES, tourist development, offer.